2018
DOI: 10.1016/j.chroma.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Method development for the certification of a ginsenoside calibration solution via liquid chromatography with absorbance and mass spectrometric detection

Abstract: The research presented here describes the development of two analytical methods for use in the certification of a ginsenoside calibration solution Standard Reference Material (SRM) 3389 consisting of seven ginsenosides: Rg1, Re, Rf, Rb1, Rc, Rb2, and Rd. The new methods utilized the liquid chromatographic (LC) separation of ginsenoside mixtures with absorbance detection (UV) and mass spectrometry (MS). Ginsenosides Rb3, Rg2, Rg3, Rh1, and Rh2 were evaluated for use as internal standards for LC/MS measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Bacillus subtilis strain SL-44 (laboratory culture), expression vector pET-28a, cloning vector pUCmt, E. coli BL21 (DE3), and DH5a were provided by Bioengineering (Shanghai) Co [20]. The specific protein sequences of the primers used in this study are shown in Table 1 [21]. Induced recombinant E. coli cells were collected by centrifugation at 8000 rpm for 5 min at 4 mg/L.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Bacillus subtilis strain SL-44 (laboratory culture), expression vector pET-28a, cloning vector pUCmt, E. coli BL21 (DE3), and DH5a were provided by Bioengineering (Shanghai) Co [20]. The specific protein sequences of the primers used in this study are shown in Table 1 [21]. Induced recombinant E. coli cells were collected by centrifugation at 8000 rpm for 5 min at 4 mg/L.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…While the primary focus of the NIH-ODS/NIST collaboration has been to provide matrix SRMs for the dietary supplement community, several calibration solution SRMs were also developed by NIST between 2011 and 2016 for catechins, hypericin, organic acids, and isoflavones. Currently, the only botanical dietary supplement ingredient calibration solution available from NIST is SRM 3389 Ginsenosides Calibration Solution ( 47 ). Another calibration solution CRM for ginsenosides is also available from the National Research Council of Canada (the NMI for Canada) as well as three pure reference standards for constituents associated with plants used as ingredients in dietary supplements 13 (see Table 4 ).…”
Section: Current Availability Of Reference Materials For Dietary Supplementsmentioning
confidence: 99%
“…Ginsenoside profiles and linoleic acid contents were analyzed for the ginseng samples at each cycle of the steaming and drying process with a selected ion monitoring (SIM) method, as listed in Table 1. Formic acid adduct ion [M-H+HCOOH] − was monitored because much higher signal abundance was observed than with deprotonated ion [M-H] − [21]. The raw data were processed using QuanLynx TM in MassLynx TM ver.…”
Section: Liquid Chromatography and Tandem Mass Spectrometry (Lc-ms/ms)mentioning
confidence: 99%